Drainage analysis on the Pondoktisuk Kebonkai Sta 1+700-1+800 road section, Nagrak District, Sukabumi Regency - Putranto Muhammad Luthfisal; Saputra Muhamad Fahmy; Pratama Mochamad Ridwan; Permadi Dio Damas; Sari Nita Kurnita; Saputri Utamy Sukmayu (BIO Web of Conferences)
This study aims to determine the rainfall distribution calculations, the consistency of rainfall data, and the drainage channel dimensions on the Pondoktisuk-Kebonkai road section Sta 1+700 – 1+800 in Nagrak District, Sukabumi Regency. The methodology used includes literature review, field observation, collection of primary data such as daily rainfall data over the past 14 years and catchment area data, as well as secondary data including field documentation and location maps. Hydrological analysis was conducted through maximum rainfall calculation, design rainfall calculation, consistency data testing, probability distribution, distribution fitting tests, rainfall intensity analysis, rainwater storage volume calculation, concentration time calculation, flood discharge analysis, and open drainage dimension calculation. The results show that the calculated water flow velocity is 1.323 m/s with a slope of 0.20%. Based on the checking process, the design meets the standard requirements for allowable water flow velocity (1.50 m/s) and slope (1%). A comparison of the planned drainage slope with the existing land slope at the study site indicates that the calculated slope is lower than the existing slope (1%), thus requiring the design of a flow breaker. The rainfall distribution calculation for the Pondoktisuk-Kebonkai road section Sta 1+700 – 1+800 in Nagrak District, Sukabumi Regency, represents all the methods used, with the Gumbel method showing the highest rainfall in all return periods. The rainfall data consistency calculation indicates that Q/n^0.5 and R/n^0.5 are smaller than their critical values, at 0.32 and 0.51 respectively, thus the data is deemed consistent. The drainage channel dimension of 80x80x100 cm with a thickness of 10 cm meets the requirements, with a calculated water flow velocity of 1.323 m/s and a slope of 0.20%, lower than the allowable limits, necessitating the inclusion of a flow breaker.